Dosimetric study for breathing-induced motion effects in an abdominal pancreas phantom for carbon ion mini-beam radiotherapy - Stengl, Christina; Muñoz, Iván Domingo; Arbes, Eric; Rauth, Evelyn; Christensen, Jeppe Brage; Vedelago, José; Runz, Armin; Jäkel, Oliver; Seco, Joao (Medical physics, 2024)
Background Particle mini-beam therapy exhibits promise in sparing healthy tissue through spatial fractionation, particularly notable for heavy ions, further enhancing the already favorable differential biological effectiveness at both target and entrance regions. However, breathing-induced organ motion affects particle mini-beam irradiation schemes since the organ displacements exceed the mini-beam structure dimensions, decreasing the advantages of spatial fractionation. Purpose In this study, the impact of breathing-induced organ motion on the dose distribution was examined at the target and organs at risk(OARs) during carbon ion mini-beam irradiation for pancreatic cancer. Methods As a first step, the carbon ion mini-beam pattern was characterized with Monte Carlo simulations. To analyze the impact of breathing-induced organ motion on the dose distribution of a virtual pancreas tumor as target and related OARs, the anthropomorphic Pancreas Phantom for Ion beam Therapy (PPIeT) was irradiated with carbon ions. A mini-beam collimator was used to deliver a spatially fractionated dose distribution. During irradiation, varying breathing motion amplitudes were induced, ranging from 5 to 15 mm. Post-irradiation, the 2D dose pattern was analyzed, focusing on the full width at half maximum (FWHM), center-to-center distance (ctc), and the peak-to-valley dose ratio (PVDR). Results The mini-beam pattern was visible within OARs, while in the virtual pancreas tumor a more homogeneous dose distribution was achieved. Applied motion affected the mini-beam pattern within the kidney, one of the OARs, reducing the PVDR from 3.78 ±±\ 0.12 to 1.478 ±±\ 0.070 for the 15 mm motion amplitude. In the immobile OARs including the spine and the skin at the back, the PVDR did not change within 3.4% comparing reference and motion conditions. Conclusions This study provides an initial understanding of how breathing-induced organ motion affects spatial fractionation during carbon ion irradiation, using an anthropomorphic phantom. A decrease in the PVDR was observed in the right kidney when breathing-induced motion was applied, potentially increasing the risk of damage to OARs. Therefore, further studies are needed to explore the clinical viability of mini-beam radiotherapy with carbon ions when irradiating abdominal regions.
Online veröffentlicht: 17. April 2024
Gesehen am 11.09.2024